Misconception Profile of Prospective Physics Teachers Assessed from Various Representations of Electricity Subjects - Muhammad Zuhdi; Ahmad Busyairi (Pascasarjana, Mataram University, 2021)
Misconception is one of the important problems that often arise in education. The objective of this study is identify misconceptions in the subject of Electricty that occur in prospective teachers. The method used in this research is descriptive method. A total of 25 pre-service physics teacher candidates at a university in the Mataram City were involved in this study. The instrument used in this study was a three-tier test. This study use a total of 40 test items. These questions are classified into two types of representation, namely; verbal and figural. The results showed that 88.1% of prospective physics teachers had misconceptions on Kirchoff's first law, 94.8% misconceptions on Kichoff's second law concept, 91.7% misconceptions on Ohm's Law concept and 85.9% on electrical sources concepts. The results of the study show that 72.3% of prospective physics teachers had misconceptions on verbal type questions and 84.2% misconceptions on figural types